Designing a waveform using LFM, NLFM for MIMO radar - Krishnam Naidu Yedla, G S; Siva Sankar Prasad, D.; Raghavendra Rao, P.; Siva Kumar, M; VenuGopala Rao, M (International Journal of Engineering and Technology, 2017)
We propose a waveform that includes Linear frequency modulation and non linear frequency modulation wave applicable for MIMO radar. The wave form consists of three segments where the boundary segment consists of LFM content and the middle segment consists of NLFM. The time frequency component in the middle segment is controlled. The range and Doppler side lobe suppression is improved. The genetic algorithm is implemented to suppress the side lobes in the auto correlation and cross correlation functions. The performance is analysed by using ambiguity function.